Pengembangan Video Edukasi “Jejak Jena Joni” Sebagai Media Pembelajaran Keberagaman Budaya Kelas IV Sekolah Dasar - Dela Perdayanti; Tita Tanjung Sari; Kadarisman Kadarisman (Jurnal Penelitian Pendidikan, 2022)
This study aims to: (1) describe the development of Jena Joni's Footsteps Educational Video as a Learning Media for Cultural Diversity for Grade IV Elementary School (2) to determine student responses to the development of Jena Joni's Footsteps Educational Video as a Learning Media for Cultural Diversity for Grade IV Elementary School. The method in this research is the Borg and Gall model development method which has been modified by Sugiono (2014). The results showed that: (1) the development in this study was declared feasible to be used as a learning medium, this was based on the results of the validation of media and material design with a percentage of 95%, 94%, respectively, with the criteria of "Very Eligible". (2) the results of product trials to 8 fourth grade students obtained the percentage value of student responses of 95.7% with the criteria of "Very Good". So it can be concluded that Jena Joni's trail educational video learning media can be declared feasible and suitable to be used as an alternative learning for teachers and students. Keywords: Educational Video, Cultural Diversity